2011
DOI: 10.1057/bm.2010.54
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corporate social responsibility on brand value

Abstract: This study analyses the impact of corporate social responsibility (CSR) on brand value, with the sample being a select group of US corporations with the best global brands. Based on the instrumental stakeholder theory, we confirm that CSR is a valid source of intangible competitive advantage. It is not used, however, to its full potential, given that CSR has a lesser impact on business performance than the size of the company and other conventional financial indicators. We contend that this undervaluation is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 64 publications
(145 reference statements)
7
91
0
14
Order By: Relevance
“…This is confirmed in our business survey, with 52% of participating managers stating that the PR and/or marketing department predominantly takes care of individual CSR projects and actions (see Figure 5). This implies that Serbian companies still principally regard CSR as a PR tool that could improve their public reputation, as well as the brand value and attributes [41]. A fifth (20%) of the business survey participants confirmed that their company employs a CSR manager, which implies a more systematic, strategic CSR approach and practice exceeding occasional charity activities.…”
Section: Csr Function Within Serbian Companies Compared To Eu Practicementioning
confidence: 99%
“…This is confirmed in our business survey, with 52% of participating managers stating that the PR and/or marketing department predominantly takes care of individual CSR projects and actions (see Figure 5). This implies that Serbian companies still principally regard CSR as a PR tool that could improve their public reputation, as well as the brand value and attributes [41]. A fifth (20%) of the business survey participants confirmed that their company employs a CSR manager, which implies a more systematic, strategic CSR approach and practice exceeding occasional charity activities.…”
Section: Csr Function Within Serbian Companies Compared To Eu Practicementioning
confidence: 99%
“…Si los consumidores ven que las marcas están abordando los temas que son importantes para ellos, es probable que continúen comprando sus productos (Verde-Nieto, 2009). Es a través de la RSE que las empresas pueden abordar directamente a los interesados, integrando a la comunidad y mejorando positivamente la reputación de la empresa (Attera, 2012;Melo, & Galan, 2011).…”
Section: Rse Y Branding: Una Aproximación Práctica Hacia Una Estrategunclassified
“…It could be argued that instead of brand value leading to high CSR ranking, CSR performance contributes to high brand value and hence high Interbrand rankings (Chen and Bouvain, 2005). Melo and Galan (2009) argues that brand value is more sensitive to CSR than a market based performance indicator. Yin Fan (2005) contents that a corporate brand is a vital part of corporate reputation management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Tsao and Chen (2011), cause related marketing (CRM), one of the most common CSR initiatives, not only increases financial gains but can also enhance a company's image and reputation which are cornerstones of the brand equity model as proposed by Aaker (1991) and Keller (2008). Melo and Galan (2009) in their study involving 54 US based corporation found that CSR impacts positively on brand value. Buil et al (2013) proposed and tested a model to better understand brand equity and found that it had a positive effect on consumers' responses using data from two European countries.…”
Section: Introductionmentioning
confidence: 99%